Detection of possible mutations in gyrA gene of ciprofloxacin-resistant Pseudomonas aeruginosa isolates from patients with lung infection - Mouly, Tonima Fairooz (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.